(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ficus bengalensis Linn, called ‘Nyagrodha’ in Ayurveda is a medicinal tree with wide range of uses in Ayurveda. The tree is having many useful parts such as bark, flower, latex, aerial roots etc. Among these, the stem bark which belongs to Panchavalkala in Ayurveda is having high demand in current scenario. Panchavalkala is the group of stem bark of five medicinal species in Ayurvedic system of medicine, which is an ingredient of many formulations. Other than this stem bark of Ficus bengalensis Linn is having many ethno medicinal uses. The drug is used for treating skin disorders, bleeding diseases, various metabolic disorders such as diabetes, dyslipidemia etc. Owing to the high demand of the drug, the adulteration of stem bark of Ficus bengalensis is common. The adulteration mostly happens with stem bark of other Ficus species as well as with the wood portion of the same instead of the bark. Thus here is an attempt to establish the genuineness of stem bark of Ficus bengalensis Linn by method of pharmacognosy and physico-chemical evaluation. The pharmacognostic evaluation includes macroscopic, microscopic evaluation of stem bark as well as the powder macroscopy and microscopy of the same by referring the standards. The physico-chemical evaluation is done by assessing various physico-chemical parameters such as foreign matter, ash values, extractive values, tannin content, sugar content, phenol content etc. Both the pharmacognostical and physico-chemical evaluation has proved the genuineness of the drug.